The life you can save : how to do your part to end world poverty / Peter Singer. - Singer, Peter, 1946- (The Life You Can Save, 2019)
In this tenth anniversary edition of 'The Life You Can Save' Peter Singer brings his landmark book up to date. In addition to restating his compelling arguments about how we should respond to extreme poverty he examines the progress we are making and recounts how the first edition transformed the lives both of readers and the people they helped. Learn how you can be part of the solution doing good for others while adding fulfillment to your own life.